2013
DOI: 10.1007/s00395-013-0387-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic polymorphisms of ion channels in the pathophysiology of coronary microvascular dysfunction and ischemic heart disease

Abstract: Conventionally, ischemic heart disease (IHD) is equated with large vessel coronary disease. However, recent evidence has suggested a role of compromised microvascular regulation in the etiology of IHD. Because regulation of coronary blood flow likely involves activity of specific ion channels, and key factors involved in endothelium-dependent dilation, we proposed that genetic anomalies of ion channels or specific endothelial regulators may underlie coronary microvascular disease. We aimed to evaluate the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 76 publications
1
108
0
2
Order By: Relevance
“…37 Previously, polymorphisms in several ion channels and in eNOS, but not in Kv1.5 channels were associated with coronary microvascular disease. 38 …”
Section: Discussionmentioning
confidence: 99%
“…37 Previously, polymorphisms in several ion channels and in eNOS, but not in Kv1.5 channels were associated with coronary microvascular disease. 38 …”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence supporting K V channels as critical modulators in the local metabolic control of coronary blood flow [3, 31, 36]. Other K + channels, such as inwardly rectifying K + channels (Kir) may also be important [11], but were not studied here. Non-selective inhibition of K V channels with 4-AP dose-dependently reduces resting coronary blood flow and decreases the balance between myocardial oxygen delivery and metabolism in response to cardiac pacing, norepinephrine, and exercise [3, 36].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs for MYH15 (codes for myosin heavy chain), VEGFA, and NT5E (associated with vascular calcification) were associated with low CFR in men but not women. In a prospective study, Fedele et al 58 identified specific polymorphisms in the gene for eNOS, and for ion channels including Kir6.2 (Katp channels), and Nav1.5 (sodium channel) in patients undergoing cardiac catheterization. SNPs in eNOS and in Kir6.2 were specific for subjects with microcirculatory dysfunction.…”
Section: The Microcirculation As a Window Into Conduit Artery Diseasementioning
confidence: 99%